1992
DOI: 10.1038/sc.1992.57
|View full text |Cite
|
Sign up to set email alerts
|

Anourethral reflex. Description of a reflex and its clinical significance: preliminary study

Abstract: A new reflex which I call the 'ano-urethral reflex' is described and its clinical significance discussed. It was studied in 16 volunteers with normal vesical and rectal functions.A concentric needle electrode was introduced into the external anal sphincter (stimulating), and another one into the external urethral sphincter (recording). The reflex response was recorded by EMG apparatus. The external urethral sphincter basal activity was increased with stimulation of the external anal sphincter. This reflex resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Moreover, it seems that the contraction of the cavernosus muscles indirectly effects urethral sphincter contraction. Previous studies demonstrate that anal sphincteric contraction evokes the ano-urethral reflex with a resulting external urethral sphincter contraction [18]. Therefore, cavernosal muscles' contraction induces contraction of both the anal and urethral sphincters.…”
Section: Role Of Cavernoso-anal Reflex During Sexual Intercoursementioning
confidence: 96%
“…Moreover, it seems that the contraction of the cavernosus muscles indirectly effects urethral sphincter contraction. Previous studies demonstrate that anal sphincteric contraction evokes the ano-urethral reflex with a resulting external urethral sphincter contraction [18]. Therefore, cavernosal muscles' contraction induces contraction of both the anal and urethral sphincters.…”
Section: Role Of Cavernoso-anal Reflex During Sexual Intercoursementioning
confidence: 96%
“…In addition to voluntarily contracting or relaxing while the other does not, both of these muscles reflexively contract or relax simultaneously (53). Electophysiological evidence demonstrated that basal activity of the external urethral sphincter was altered by electric stimulation of the EAS in healthy volunteers (52). In addition, vigorous distension of anal sphincter led to inhibition of urethra and anal sphincter activity in most spinal cord-injured patients (48).…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the latency which is the period between the start of iced saline infusion into the rectum and the onset of the rectal tone response. The latency was measured by the switch-inflation apparatus (Avicina Medical Instruments, Cairo, Egypt) [19] .…”
Section: Methodsmentioning
confidence: 99%